Assessing for interaction between APOE ε4, sex, and lifestyle on cognitive abilities. (4th June 2019) - Lyall, Donald M.; Celis-Morales, Carlos; Lyall, Laura M.; Graham, Christopher; Graham, Nicholas; Mackay, Daniel F.; Strawbridge, Rona J.; Ward, Joey; Gill, Jason M.R.; Sattar, Naveed; Cavanagh, Jonathan; Smith, Daniel J.; et al.
Abstract : Objective: To test for interactions between APOE ε4 genotype and lifestyle factors on worse cognitive abilities in UK Biobank. Methods: Using UK Biobank cohort data, we tested for interactions between APOE ε4 allele presence, lifestyle factors of alcohol intake, smoking, total physical activity and obesity, and sex, on cognitive tests of reasoning, information processing speed, and executive function (n range = 70, 988–324, 725 depending on the test). We statistically adjusted for potential confounders of age, sex, deprivation, cardiometabolic conditions, and educational attainment. Results: There were significant associations between APOE ε4 and worse cognitive abilities, independent of potential confounders, and between lifestyle risk factors and worse cognitive abilities; however, there were no interactions at multiple correction-adjusted p < 0.05, against our hypotheses. Conclusions: Our results do not provide support for the idea that ε4 genotype increases vulnerability to the negative effects of lifestyle risk factors on cognitive ability, but rather support a primarily outright association between APOE ε4 genotype and worse cognitive ability.